Fertilización de soya (Glicine max) aplicando niveles de fósforo y cloruro de potasio en la zona de jumon provincia del Oro - Salguero Saltos, Juana Haydee (2013)
With the objective of comparing the agronomic efficiency of phosphorus fertilizer levels and potassium chloride in the cultivation of soya,was conducted field research using a completely randomized design with 4 treatments and 4 replications, using three different doses plus a control. The results indicate that statistical differences were found in all the variables under study being the most effective dose for 150P – 175KCl flat height variables , loading height of the first fruit , number of pods per plant and 100 seed weight , while the best dose for grain yield was 100P- 125KCl . The best benefit -cost treatment presented 100P- 125KCl higher income with a value of 1.89. All responded positively treatments versus control performance therefore concluded that it is feasible high response to the application of fertilizers based on phosphorus and potassium, which is reflected by increases in yields with the application of phosphate sources and potassium with the control. Application levels of phosphorus and potassium chloride was presented as a good alternative agronomic fertilization in soils of the study site although not suitable for cultivation